2019
DOI: 10.3390/nu11112728
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Disability and Nutrition: Findings from a Population-Based Case Control Study in Rural Bangladesh

Abstract: Background: Evidence regarding the complex relationship between childhood disability and malnutrition is limited in low and middle income countries. We aimed to measure the association between childhood disability and malnutrition in rural Bangladesh. Method: We conducted a population-based case control study among children aged <18 years in a rural sub-district (i.e., Shahjadpur) in Bangladesh. Children with permanent disability (i.e., Cases) and their age/sex-matched peers (i.e., Controls) were identified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…Observation of similar trends in the proportions of severely underweight among children with a disability was 293 (43.3%) vis-a-vis 81 (12.1%) among children without a disability was seen. [ 1 ] These study findings and the present study have found similar results, though the parameters for the nutritional status used were different (weight and height for age and weight for height instead of WHO BMI centiles). Because of these inherent differences in the methods used in the evaluation the nutritional status, comparison in the rates of overnutrition (overweight and obesity) was not possible.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Observation of similar trends in the proportions of severely underweight among children with a disability was 293 (43.3%) vis-a-vis 81 (12.1%) among children without a disability was seen. [ 1 ] These study findings and the present study have found similar results, though the parameters for the nutritional status used were different (weight and height for age and weight for height instead of WHO BMI centiles). Because of these inherent differences in the methods used in the evaluation the nutritional status, comparison in the rates of overnutrition (overweight and obesity) was not possible.…”
Section: Discussionsupporting
confidence: 87%
“…Jahan I et al ., Bangladesh, in 2019 showed significant differences in rates of severely wasted children among of whom 25 (20.4%) when compared to 7 (2.7%) children without disability. [ 1 ] The rate of severe stunting was also notably higher i.e. 599 (48.0%) compared to children without disability, where it was only 115 (9.1%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research was unable to find the basic relationship between early childhood disability and associated factors. These studies may suffer from various limitations, such as inadequate focus on specific (cognitive) disability [ 18 ], use of limited statistical methods [ 19 ], and small sample size with the specific region [ 20 ]. Although, some of the studies used multivariable linear and binary logistic regressions to identify the potential determinants of childhood disability [ 18 , 21 , 22 ], none of the studies used ordinal logistic regression to find out the child, family, and community-level determinants.…”
Section: Introductionmentioning
confidence: 99%